ETHNOBOTANICAL ASSESSMENT OF PLANTS USED FOR THE TREATMENT OF MALARIA IN KIYAWA TOWN, JIGAWA STATE NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The aim of this study was to make an inventory of medicinal plants for the treatment of malaria and examine how people used them to treat the disease in Kiyawa Town, Jigawa State,with a view to providing benchmark information for health practitioners and policy makers to enhance the medical system in theState. A total of nine respondents (four traditional healers and five herbalists) were sampled using snowball sampling technique. Structured interview was conducted with the respondents to elicit information on the type species used for the preparation of remedies for malaria treatment, methods of administration of such preparations as well as conservation of species with medicinal value. This study found that Senna occidentalis and Azadirachta indica were the common plants used for the treatment of malaria in the area through oral administration of decoction made from their leaves. This study recommended that integratedresearch should be conducted in this field because traditional knowledge is continuously changing, evolving and adapting to the new social and environmental conditions in the area.
Keywords: biotic diversity, medicinal plants, remedies